Tailored cancer therapy by magnetic nanoparticle hyperthermia: A virtual scenario simulation method. (November 2022) - Montes-Robles, Roberto; Montanaro, Hazael; Capstick, Myles; Ibáñez-Civera, Javier; Masot-Peris, Rafael; García-Breijo, Eduardo; Laguarda-Miró, Nicolás; Martínez-Máñez, Ramón
Highlights: A scenario for optimized tailored magnetic nanoparticle-mediated hyperthermia. We aim to heat only tumoral cells avoiding the affection to healthy tissues. Different MNPs application scenarios have been studied. The method induces hyperthermal temperature in 90% of the tumoral tissues. This virtual method helps real and personalized cancer therapy planning. Abstract: Background and objective: Hyperthermia is a cancer treatment aiming to induce cell death by directly warming cancerous tissues above 40 °C. This technique can be applied both individually and together with other cancer therapies. The main challenge for researchers and medics is to heat only tumoral cells avoiding global or localized heating of sane tissues. The objective in this study is to provide a realistic virtual scenario to develop an optimized multi-site injection plan for tailored magnetic nanoparticle-mediated hyperthermia applications. Methods: A three-dimensional model of a cat's back was tested in three different simulation scenarios, showing the impact of magnetic nanoparticles in each specific environment configuration. Results: As a result of this study. This simulation method can, minimising the affection to healthy tissue. Conclusions: This virtual method will help real and personalized therapy planning and tailor the dose and distribution of magnetic nanoparticles for an enhanced hyperthermia cancer treatment.